Impactos dos investimentos em P&D nos depósitos de patentes nos países do BRICS - Fialho, Bruno Germani (2015)
Patents, for being in possession of inside information relating to technological innovations that will be on the market in the coming years, are becoming increasingly important in scientific studies. Patent analysis studies can be quantitative or qualitative. With patents, someone can make an analysis of inventive step from a subject matter, be it a country, a company or a technology as well as its relations with the other "players" in the market. This research analyzes the correlations between investments in R&D of BRICS countries and patent applications to see whether these investments are replicated in the knowledge generated in those countries. It were also collected data publications and scientific articles, and the GDP to supplement the correlation study. Analyses are performed for each country and discussed the results. Few studies relate patents for areas in order to obtain an overview of a country facing its patents for a certain period. With this study, we sought to exactly analyze all the patents published in Brazil, identifying its areas and countries of origin or destination. Through the correlations between variables raised to the BRICS countries, this study analyzed the strengths and weaknesses of each country.